Standardization of Light Transmission Aggregometry for Diagnosis of Platelet Disorders: An Inter-Laboratory External Quality Assessment - Althaus, Karina; Zieger, Barbara; Bakchoul, Tamam; Jurk, Kerstin; On behalf of THROMKID-Plus Studiengruppe der Gesellschaft für Thrombose- und Hämostaseforschung (GTH) und der Gesellschaft für Pädiatrische Onkologie und Hämatologie (GPOH) (Thrombosis and Haemostasis, 2019)
Several in vitro platelet function tests are available for the diagnosis of inherited platelet function disorders. Currently, the light transmission aggregometry (LTA) is recommended as one of the first-step tests. LTA is available in most specialized hemostasis laboratories. Although the LTA is accepted as a ‘gold standard’ assay for the evaluation of platelet function, its standardization in the clinical practice is still challenging. The GTH-based THROMKID-Plus Study Group has performed an inter-laboratory trial in Germany and Austria. Five different agonists were selected according to the Scientific and Standardization Committee/International Society on Thrombosis and Haemostasis recommendations and shipped in 3 different sets (one should represent a healthy control and two should simulate platelet function disorders) to 15 specialized laboratories in Germany and Austria. Agonists were analyzed by APACT or PAP4/8 aggregometer using platelet-rich plasma from healthy donors. In addition, laboratory-internal platelet agonists were tested in platelet-rich plasma from a healthy donor. All laboratories (9 used APACT, 6 used PAP4/PAP8) showed very consistent data regarding the maximum percentage of aggregation induced by the tested agonists and identified the differential diagnosis of the simulated platelet function disorders with one exception, which was due to technical problems. In contrast, there was a high variability of the laboratory-internal inductors regarding reagent type, concentrations and pathological cut-off values. Our study showed that the shipment of agonists is suitable for an inter-laboratory survey of LTA. However, there is still a remarkable need for standardization of agonist reagents and their concentration as well as for definition of reference ranges.
Keywords: platelets; light transmission aggregometry; inherited platelet disorders